Temporary Ectopic Implantation of an Amputated Leg Using the Distal Runoff Vessel of the Anterolateral Thigh Flap Followed by Subsequent Prefabricated Chimeric Replantation. Issue 1 (January 2019) - Wang, Kuan-Chih; Hung, Kuo-Shu; Chang, Tzu-Yen; Wu, Po-Ting; Lee, Yao-Chou
Abstract : Aim: Infrapopliteal replantation is indicated in selected patients. When the patient is hemodynamically unstable or the amputation site is severely contaminated, temporary ectopic implantation of the amputated limb is an option. To the best of our knowledge, this is the first case report using the distal runoff vessel of the anterolateral thigh flap for temporary ectopic implantation of an amputated leg followed by replantation with the prefabricated anterolateral thigh flap. Patient and Methods: A 28-year-old male driver had left leg avulsion amputation after a car accident. Because of concerns about the high-energy trauma mechanism and extensive trauma zone, temporary ectopic implantation was planned to avoid a lengthy replantation procedure and to enable future replantation. The amputated leg was implanted to the thigh using the distal runoff vessel of the descending branch of the lateral circumflex femoral system in the preservation of proximal cutaneous perforator. When the patient became hemodynamically stable and the amputated stump was relatively clean and healthy, we replanted the amputated leg with the prefabricated anterolateral thigh flap on day 7. Results: The replanted leg and anterolateral thigh flap survived well after the procedure. At the 15-month follow-up, the patient could walk independently. There was no need for custom-made shoes because there was no obvious leg length discrepancy and the flap was not bulky. Conclusions: We believe that the distal runoff vessel of the descending branch of the lateral circumflex femoral system can not only serve as a recipient site for temporary ectopic implantation but also enable the harvest of a prefabricated anterolateral thigh flap with the amputated part at the replantation stage. This prefabricated tissue containing the anterolateral thigh flap and the amputated part needs only 1 set of vascular anastomosis to accomplish replantation and simultaneous revascularization of the anterolateral thigh flap. Most importantly, this ectopically prefabricated chimeric tissue minimizes the need for extensive bone shortening after radial debridement by providing sufficient soft tissue coverage at the replantation stage.